Scaling property in one-nucleon removal reactions induced by exotic nuclei - 方德清 付瑶 孙小燕 蔡翔舟 郭威 田文栋 王宏伟 马余刚 (Chinese physics C, 2009)
Assuming a core plus valence nucleon structure, one-nucleon removal reaction is investigated within the framework of few-body Glauber theory. Fermi-type distribution is used for the core density, while the wavefunction of the valence nucleon is calculated by solving the single particle eigenvalue problem of the SchrSdinger equation with the Woods-Saxon potential. The parallel momentum distribution （P//） of the fragments is calculated for isotopes with 3 〈 Z 〈 18. A remarkable scaling property is observed from the dependence of the dimensionless quantity P^2 v/R^2 e on the full width at half maximum of the parallel momentum distribution （FWHMp//）. R^2 v/R^2 c is a measure of the exotic extent of the nuclear halo. Based on the obtained 2 2 scaling law, FWHMp// can be used as an experimental observable to extract R^2 v/R^2 c and measure the exotic extent for the nuclear halo.